Share Repurchase as a Takeover Defense - Sinha, Sidharth (Journal of Financial and Quantitative Analysis, 1991)
This paper presents a model in which managers of firms that are takeover targets use debt-financed share repurchase to bond themselves to reduce perquisite consumption and increase investment in the firm. The resulting value increase makes the firm a less attractive target. The optimal level of share repurchase is the result of a trade-off between the benefit of a reduced probability of takeover and the cost of an increased probability of bankruptcy. Unlike earlier explanations of defensive repurchases, which are based on information signalling or control of voting rights, this explanation is independent of the extent of shareholding by target management.